Perceptions of and Behavioral Intentions towards Learning Artificial Intelligence in Primary School Students - Chai, Ching Sing; Lin, Pei-Yi; Jong, Morris Siu-Yung; Dai, Yun; Chiu, Thomas K. F.; Qin, Jianjun (Educational Technology ＆ Society, 2021)
Artificial Intelligence (AI) is increasingly popular, and educators are paying increasing attention to it. For students, learning AI helps them better cope with emerging societal, technological, and environmental challenges. This theory of planned behavior (TPB)-based study developed a survey questionnaire to measure behavioral intention to learn AI (n = 682) among primary school students. The questionnaire was administered online, and it measured responses to five TPB factors. The five factors were (1) self-efficacy in learning AI, (2) AI readiness, (3) perceptions of the use of AI for social good, (4) AI literacy, and (5) behavioral intention. Exploratory factor analysis and a subsequent confirmatory factor analysis were used to validate this five-factor survey. Both analyses indicated satisfactory construct validity. A structural equation model (SEM) was constructed to elucidate the factors' influence on intention to learn AI. According to the SEM, all factors could predict intention to learn AI, whether directly or indirectly. This study provides new insights for researchers and instructors who are promoting AI education in schools.